MARKETING COMMUNICATION MODEL OF THE MUHAMMADIYAH COMMUNITY ORGANIZATION IN MEDAN CITY IN BUILDING THE ORGANIZATION'S BRAND IMAGE - All Rizky Ramadhan Siregar; Dewi Kurniawati; Maulana Andinata Dalimunthe (Journal Analytica Islamica, 2025)
This study aims to analyze the marketing communication model implemented by Muhammadiyah in Medan City to build its brand image as a da'wah (Islamic propagation) organization that is adaptive to contemporary developments. The research is motivated by the need for non profit, especially religious, organizations to formulate effective communication strategies amidst rapid digital transformation and changing communication patterns in society. The study is grounded in key theoretical frameworks,including organizational communication theory, marketing communication theory, and brand image theory. A descriptive qualitative approach was adopted, with data collected through in-depth interviews, participatory observation, and documentation. Thematic analysis was employed using coding techniques to identify key themes based on informant narratives. The findings reveal that Muhammadiyah's marketing communication model in Medan is built through synergy between internal organizational communication, which emphasizes a collective collegial approach, and external communication through social and mass media as the main channels for disseminating da'wah messages. Core values of da'wah bil hal da'wah through concrete actions such as education, healthcare, and community empowerment form the foundation for shaping a positive public perception of Muhammadiyah. However, several challenges remain, such as low levels of digital literacy among grassroots communities and cultural resistance to change. This study recommends strengthening digital communication capacity, adopting educational and participatory approaches to delivering religious messages, and implementing inclusive strategies to engage marginalized groups. translatekan kebahasa Indonesia.